Risks facing islamic banks amid the shift towards the digital economy and ways to manage them - Ounnassa, Hamdi; Abderrahmane, Maidi (International journal of economic perspectives, 2025)
The global trend towards the digital economy has compelled Islamic banks to keep up with developments by providing high-quality services that save time, effort, and enhance precision in information while reducing costs. They respond swiftly to their clients’ needs using the internet and various modern technological methods. Islamic banks, similar to other financial institutions, have benefited from the outcomes of this digital transformation. However, this has also exposed them to numerous risks, necessitating them to address and devise ways and methods to manage these risks.